A 7.5‐Mb duplication at chromosome 11q21‐11q22.3 is associated with a novel spastic ataxia syndrome. Issue 2 (27th December 2014) - Johnson, Janel O.; Stevanin, Giovanni; van de Leemput, Joyce; Hernandez, Dena G.; Arepalli, Sampath; Forlani, Sylvie; Zonozi, Reza; Gibbs, J. Raphael; Brice, Alexis; Durr, Alexandra; Singleton, Andrew B.; Stacy (Chair), Mark; et al.
Abstract Background The autosomal dominant spinocerebellar ataxias are most commonly caused by nucleotide repeat expansions followed by base‐pair changes in functionally important genes. Structural variation has recently been shown to underlie spinocerebellar ataxia types 15 and 20. Methods We applied single‐nucleotide polymorphism (SNP) genotyping to determine whether structural variation causes spinocerebellar ataxia in a family from France. Results We identified an approximately 7.5‐megabasepair duplication on chromosome 11q21‐11q22.3 that segregates with disease. This duplication contains an estimated 44 genes. Duplications at this locus were not found in control individuals. Conclusions We have identified a new spastic ataxia syndrome caused by a genomic duplication, which we have denoted as spinocerebellar ataxia type 39. Finding additional families with this phenotype will be important to identify the genetic lesion underlying disease. © 2014 International Parkinson and Movement Disorder Society